2017
DOI: 10.1111/acps.12846
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders and prospective suicidality in young adults: a population‐based cohort study

Abstract: Depressive episodes have a strong, independent, and robust association with prospective suicidality. The association between manic episodes and suicidality, on the other hand, was dependent on the analysis and deserves further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…Overall, we found 7 records reporting on the association between depressive symptoms and risky sexual behavior, [44][45][46][47][48][49][50] 10 for substance use, 45,48,49,[51][52][53][54][55][56][57] 4 for delinquency, [58][59][60][61] 3 for self-harm [62][63][64] and 11 for suicidal behavior (2 of which were included in the systematic review). [65][66][67][68][69][70][71][72][73][74][75] Three studies reported on both risky sexual behavior and substance use, separately. 45,48,49 One study included in the systematic review reported an index of risky behaviors (combining behaviors such as unsafe sexual practices, violent behaviors and rule breaking).…”
Section: [Insert Figure 1 Around Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we found 7 records reporting on the association between depressive symptoms and risky sexual behavior, [44][45][46][47][48][49][50] 10 for substance use, 45,48,49,[51][52][53][54][55][56][57] 4 for delinquency, [58][59][60][61] 3 for self-harm [62][63][64] and 11 for suicidal behavior (2 of which were included in the systematic review). [65][66][67][68][69][70][71][72][73][74][75] Three studies reported on both risky sexual behavior and substance use, separately. 45,48,49 One study included in the systematic review reported an index of risky behaviors (combining behaviors such as unsafe sexual practices, violent behaviors and rule breaking).…”
Section: [Insert Figure 1 Around Here]mentioning
confidence: 99%
“…Three studies did not report poolable data and were thus not included in the meta-analysis. One study reported findings as a regression coefficient, 75 another reported a risk ratio without the absolute numbers, 67 and another study reported an index of risky behaviors. 76 All three studies reported a positive association between depressive symptoms and risky behaviors, reinforcing the results of the meta-analysis.…”
Section: [Insert Table 1 Around Here]mentioning
confidence: 99%
“…Своевременная диагностика и лечение БР имеют важное значение для замедления развития эпизодов расстройства настроения, что позволит снизить вероятность формирования когнитивных нарушений, ухудшение качества жизни, а также предотвратить преждевременную смертность от самоубийств и сердечно-сосудистых заболеваний [33].…”
Section: __________________________unclassified
“…Применение скрининговых методик для ранней диагностики риска ставляется актуальной в свете увеличения удельного веса этой патологии в пубертатном периоде [7,8]. Важным аспектом данной проблемы является трудность диагностики, во многом связанная с атипичностью клинической картины субдепрессивных, депрессивных, гипоманиакальных, маниакальных и смешанных эпизодов, дебютирующих в подростковом возрасте, ее полиморфностью и синдромальной незавершенностью, обусловленной особенностями формирующейся подростковой психики [9].…”
Section: Introductionunclassified